The use of aminoguanidine, a selective inducible nitric oxide synthase inhibitor, to evaluate the role of nitric oxide on periapical healing - Ali Reza Farhad; Seyed Mohammad Razavi; Parnian Alavi Nejad (Wolters Kluwer Medknow Publications, 2011)
Background: Nitric oxide (NO) is one of the many chemical mediators involved in inflammatory processes. In addition to periapical inflammation, NO can have a role in periapical healing. The purpose of this study was to evaluate the effect of aminoguanidine (AG) as a selective inhibitor of inducible nitric oxide synthase (iNOS) on the degree of healing response of periapical lesions of the canine teeth of cats. Methods: In this interventional experimental study, the root canals of 48 cat canine teeth were infected with cat dental plaque and sealed. After induction of periapical lesions, root canal therapy (RCT) was performed. On the day of RCT phase, the cats were administered either AG (experimental group) or normal saline (control group), which was continued on a daily basis until the day of sacrifice. Four canine teeth in one cat served as negative and positive controls. The animals were sacrificed 6 weeks after RCT. The healing response of the periapical zones was analyzed histologically. The mean scores of healing for the two groups were compared using Mann-Whitney U test. Results: The mean scores of healing for the AG group (2.45±0.508) were significantly higher than those of the control group (2±0.510) (P<0.05). Conclusion: The use of an iNOS selective inhibitor such as AG can accelerate the healing process in periapical lesions.